An emulsion electrospun nanofibrous scaffold loaded with glial cell line-derived neurotrophic factor for nerve regeneration - Gregory, Holly N.; Johnson, Louis D. V.; Phillips, James B. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDamage to peripheral nerves is common in major trauma cases, and current options for surgical repair are often not sufficient to promote satisfactory recovery of sensory and motor function. In this study we describe the development of a biomaterial scaffold with aligned nanofibrous topography and encapsulated neurotrophic factor, designed to direct and enhance axonal regeneration and so effectuate faster return of function.MethodsGlial cell line-derived neurotrophic factor (GDNF) was loaded into aligned polycaprolactone (PCL) nanofibres using emulsion electrospinning, and the biomaterial was characterised alongside random and aligned PCL scaffolds without growth factor.Results and discussionThis fabrication route produced fine and uniform nanofibres with sustained release of GDNF over at least four weeks, and the aligned topography was able to orientate the growth of Schwann cells. Finally, the GDNF-loaded aligned nanofibrous scaffold significantly enhanced and directed the outgrowth of primary rat neurons cultured on its surface, demonstrating its promise as a pro-regenerative biomaterial for the surgical repair of nerve injury.